Hudde en zijn gesmolten microscooplensjes - Cocquyt, Tiemen; Bolt, Marvin; Korey, Michael (Studium, 2018)
In this article, the role of Johannes Hudde as material instigator of the blossoming microscopic cul- ture in the late seventeenth-century Netherlands is examined. The simple ball lens microscopes that Hudde developed in the late 1650s saw widespread adoption, yet surprisingly little is known about their origin. After reflecting on the contemporary literature on Hudde’s lenses, their optical properties are discussed and compared with those of thin, ground lenses. Next, an account is given of a reconstruction experiment, performed in the Corning Museum of Glass (NY), where the manufacturing processes for both Hudde’s flameworked lenses and for common ground lenses were put to test. It is explained how this gave insight in the unique advantages of Hudde’s lens making innovation. Taking this further, the significance of glass melting techniques for the broader historiography of the microscope and its lens production is evaluated. Finally, it is argued how shifting demands in the c. 1700 microscope market meant that Hudde’s, otherwise very successful, lenses were gradually abandoned.